PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB BERFITUR AUDIO PADA MATERI HEWAN HERBIVORA UNTUK SISWA SDLB-A DI SLB PGRI KALITIDU - Amir, Day Ramadhani; Abelianti, Nurlita; Amin, Ahmad Kholiqul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students who are blind require educational aids that cater to their specific learning characteristics, particularly by leveraging their sense of hearing. Observations and interviews at SLB PGRI Kalitidu revealed that support teachers rely on Braille books, verbal explanations, and YouTube audio content to teach science. These tools are not yet integrated into a single platform designed to meet the specific learning needs of visually impaired students. However, teachers noted that two students at the school (SDLB-A) possess good hearing abilities, making audio-based media a viable option for their learning activities. This study aimed to develop a web-based learning medium featuring audio named "SuaraEdu"—focused on the topic of herbivores, and to assess its suitability through expert validation and teacher feedback. The study employed the Research and Development (R&D) method using the ADDIE model, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. Participants included media experts, subject matter experts, and support teachers (as the end-users). Data were collected through observation, interviews, documentation, expert validation sheets, and teacher feedback questionnaires. The findings indicate that the media achieved a 92% suitability rating from media experts (categorized as "Highly Suitable"), a 97% rating from subject matter experts ("Highly Suitable"), and a 96% positive response from support teachers ("Excellent"). These results demonstrate that SuaraEdu is a suitable and practical tool for teaching about herbivores at SLB PGRI Kalitidu.